2015
DOI: 10.1016/j.exger.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor 1, fibroblast apoptosis resistance, and aging-related susceptibility to lung fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disorder with unknown cause and no effective treatment. The incidence of and mortality from IPF increase with age, suggesting that advanced age is a major risk factor for IPF. The mechanism underlying the increased susceptibility of the elderly to IPF, however, is unknown. In this study, we show for the first time that the protein level of plasminogen activator inhibitor 1 (PAI-1), a protease inhibitor which plays an essential role in the control of fibrinoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 71 publications
(110 reference statements)
4
64
0
1
Order By: Relevance
“…Thus, while acknowledging that differences in the accumulation of monocyte/macrophages and fibrocytes, or decreased levels of CCL12 or IFN-g, might contribute to the discordant fibrotic outcomes in these two approaches, we went on to investigate the apoptotic susceptibility of murine lung mesenchymal cells. Studies increasingly support the hypothesis that impaired apoptosis contributes to myofibroblast accumulation in lung fibrosis (8,(11)(12)(13)(41)(42)(43). Consistent with the initial characterization of XIAP-deficient mice (31), our investigation revealed that mesenchymal cells from the XIAP-deficient mice did not demonstrate increased susceptibility to Fasmediated apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, while acknowledging that differences in the accumulation of monocyte/macrophages and fibrocytes, or decreased levels of CCL12 or IFN-g, might contribute to the discordant fibrotic outcomes in these two approaches, we went on to investigate the apoptotic susceptibility of murine lung mesenchymal cells. Studies increasingly support the hypothesis that impaired apoptosis contributes to myofibroblast accumulation in lung fibrosis (8,(11)(12)(13)(41)(42)(43). Consistent with the initial characterization of XIAP-deficient mice (31), our investigation revealed that mesenchymal cells from the XIAP-deficient mice did not demonstrate increased susceptibility to Fasmediated apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…The ratio of p53 S18P to p53 is significant increased with bleomycin treatment; silencing PAI‐1, however, attenuates bleomycin‐stimulated increase in the ratio (Fig. D,H), suggesting that PAI‐1 stimulates p53 phosphorylation at serine 18, a critical phosphorylation site for the stability of p53 protein (Huang et al ., , ), independence of its effect on p53 protein abundance. Associated with inhibition of p53 and p21 expression as well as stimulation of Rb phosphorylation, PAI‐1 shRNA ameliorates bleomycin‐mediated suppression of proliferating cell nuclear antigen (PCNA) expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Posttranslational modifications, including phosphorylation and ubiquitination, play a critical role in p53 protein stability and transactivation function (Huang et al ., ; Marzec et al ., ). Phosphorylation of p53 at serine 15 and serine 20 (serine 18 and serine‐23 in rodents) prevents the binding of p53 to murine double minute 2 (MDM2), a major E3 ubiquitin ligase involved in p53 degradation, and thereby stabilizes p53 protein (Huang et al ., , ). Our studies show that treatment of rat ATII (L2) cells with PAI‐1 protein increases, whereas silencing PAI‐1 with PAI‐1 shRNA or inhibition of PAI‐1 activity with a small molecule PAI‐1 inhibitor TM5275 decreases, p53 phosphorylation at serine‐18 residue, suggesting that PAI‐1 increases p53 protein probably by increasing p53 serine 15 and/or serine 20 phosphorylation and thereby suppressing its degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Latent complexes of TGF‐β1 bind with the latent TGF‐β1 binding proteins 1 and 2 (LTBP1/2; ltbp1/2 ), which expose them to the matrix for activation (72). Serpine‐1 , a member of the serine proteinase inhibitor superfamily and the principal inhibitor of tissue plasminogen activator and urokinase, is associated with collagen accumulation and myofibroblast survival (73), which protects fibroblasts from apoptosis (74) and alveolar injury (75). Dysregulated angiogenic responses in patients with IPF were associated with increases in systemic tsp1 (76), and thrombospondin‐1 is implicated in the activation of latent TGF‐β1 (77).…”
Section: Discussionmentioning
confidence: 99%